Innovation in tourism services in the context of the shared economy - Corrêa, Cynthia (Revista Hipótese, 2017)
In the sharing economy scenario, innovations consolidate as a basic element to promote the growth of the tourism sector. Through literature review and documentary analysis, this paper presents innovation as inseparable from the development of this economic activity, from the four types of innovation outlined in the third edition of the Oslo Manual. Thus, innovation is crucial to stimulate the advancement of tourism services, benefiting all stakeholders.